"Booster" or "obstacle": Can coal capacity cut policies moderate the resource curse effect? Evidence from Shanxi (China). (March 2022) - Yao, Xilong; Wang, Hualing; Shao, Shuai; Li, Xiaoyu; Guo, Zhi
Abstract: China's recent coal capacity cut policies are expected to promote an energy supply-side revolution. However, their real impacts are still uncertain, especially for coal resource-based regions. Based on a dynamic computable general equilibrium (DCGE) model, this is the first study to investigate the effects of output-controlled and investment-controlled coal capacity cut policies on macroeconomy and the environment (including carbon emissions) in Shanxi province, the most typical representative of coal resource-based regions in China. The results show that the output-controlled coal capacity cut policy not only can reduce sulfur emissions and carbon emissions, but also can promote long-term economic growth and households' income. Moreover, although the output-controlled coal capacity cut policy reduces financial revenues, this kind of policy can weaken the excessive inflow of production factors in coal industry and promote the development of non-coal industries. On the other hand, the investment-controlled coal capacity cut policy does not cause labor outflow from coal industry. This kind of policy can also reduce sulfur emissions and carbon emissions, though it shows a negative impact on macroeconomic factors, such as gross domestic product and welfare. We find that only the output-controlled coal capacity cut policy can effectively moderate the resource curse effect in coal resource-based regions, and therefore, this kind of policy should be the first choice of the Chinese government. Highlights: We develop a dynamic computable general equilibrium (DCGE) model. We explore the economic and environmental effects of coal capacity cut policy in Shanxi (China). Output-controlled coal capacity cut policy reduces emissions and promotes GDP growth. Investment-controlled coal capacity cut policy has negative impacts on GDP and welfare. Output-controlled coal capacity cut policy can moderate the resource curse effect.